Exit Survey of Women with HSDD Treated With Bremelanotide Demonstrated Meaningful Treatment Benefits [28G]. (May 2018) - Koochaki, Patricia; Revicki, Dennis; Wilson, Hilary; Pokrzywinski, Robin; Jordan, Robert; Lucas, Johna
Abstract : INTRODUCTION: Bremelanotide, an investigational new drug, demonstrated clinically meaningful improvements in desire and decrease in distress in premenopausal women with hypoactive sexual desire disorder (HSDD) in the phase 3 RECONNECT studies. Here we present outcomes from exit surveys completed by a subset of subjects from RECONNECT, with a focus on the meaningfulness of treatment benefit. METHODS: Study subjects were randomized to self-administer bremelanotide (1.75 mg) or placebo subcutaneously via auto-injector pen as desired prior to sexual activity for 24 weeks. Upon study completion, 242 women participated in a quantitative exit survey. RESULTS: Among subjects who completed the survey, mean(SD) duration of HSDD was 55.2(48.1) months; symptoms at baseline included decreased sexual interest and desire, decreased arousal, changes in sexual satisfaction/orgasm, and physical changes in lubrication. Overall meaningful benefit as determined using the exit survey was seen in 58.8% of the bremelanotide group and 27.1% of the placebo group (p<0.0001). The bremelanotide group reported a meaningful increase in sexual desire and responsiveness to their partners initiating sexual activity (51.0% and 53.9%, respectively) compared to placebo (20.7% and 25.7%, respectively; p<0.0001 for both). Treatment with bremelanotide was associated with significant improvement in sexual satisfaction (56.9% vs 25.7%; p<0.0001), and meaningful improvements in mental (52.0% vs 25.7%; p<0.0001) and physical (64.7% vs 21.4%; p<0.0001) arousal. Overall, 62.4% of participants rated their experience with the device as excellent or very good. CONCLUSION: Women randomized to bremelanotide consistently reported meaningful treatment benefits compared to placebo, which reiterated the primary outcomes in the overall RECONNECT study population.